2022
DOI: 10.2174/1568009621666210720142542
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Peripheral Neuropathy: Diagnosis and Management

Abstract: : Peripheral neuropathy comes in all shapes and forms and is a disorder which is found in the peripheral nervous system. It can have an acute or chronic onset depending on the multitude of pathophysiologic mechanisms involving different parts of nerve fibers. A systematic approach is highly beneficial when it comes to cost-effective diagnosis. More than 30 causes of peripheral neuropathy exist ranging from systemic and auto-immune diseases, vitamin deficiencies, viral infections, diabetes, etc. One of the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 252 publications
0
3
0
Order By: Relevance
“…DIPNs are caused by damage to the peripheral sensory nervous system as an unintended, off-target effect from many different types of small molecular drugs to treat cancers, including both cytotoxic and targeted therapeutics ( e.g . multi-kinase inhibitors or MKIs) (Peltier and Russell 2002; Visovsky 2003; Kane et al 2006; Breccia and Alimena 2010; Cortes et al 2010; Rey et al 2015; Roy et al 2019; Merheb et al 2022). Treatment options for patients experiencing painful DIPNs are highly limited and non-specific (Shah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…DIPNs are caused by damage to the peripheral sensory nervous system as an unintended, off-target effect from many different types of small molecular drugs to treat cancers, including both cytotoxic and targeted therapeutics ( e.g . multi-kinase inhibitors or MKIs) (Peltier and Russell 2002; Visovsky 2003; Kane et al 2006; Breccia and Alimena 2010; Cortes et al 2010; Rey et al 2015; Roy et al 2019; Merheb et al 2022). Treatment options for patients experiencing painful DIPNs are highly limited and non-specific (Shah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature underscores the importance of comprehensive treatment approaches in RA, emphasizing the need for interventions that not only control disease activity but also address functional impairments and quality of life. However, there is a gap in understanding how combined therapeutic modalities can optimize these outcomes, particularly in the context of RA with concurrent PN (10)(11)(12). This research aims to fill the identified gap by comparing the effectiveness of combined NMES and DMARD therapy versus DMARD therapy alone in enhancing gait and reducing fall risks in RA patients with PN.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 20 million people in the United States with PN, 5,6 approximately 40% are cancer survivors who develop chemotherapy-induced PN (CIPN), 7 and 50% are adults with diabetic PN 5 . Although its antecedents are sometimes difficult to trace, there are more than 30 known causes of PN, which include physical injury, autoimmune diseases, imbalanced diet (such as obesity), diabetes, infections, and chemotherapy drugs 8,9 . In many cases, however, no specific cause (idiopathic) can be identified 5 .…”
mentioning
confidence: 99%
“…5 Although its antecedents are sometimes difficult to trace, there are more than 30 known causes of PN, which include physical injury, autoimmune diseases, imbalanced diet (such as obesity), diabetes, infections, and chemotherapy drugs. 8,9 In many cases, however, no specific cause (idiopathic) can be identified. 5 Moreover, as current rates of obesity and metabolic irregularities continue to rise in the US population, the ratio of individuals developing PN-related symptoms as they age may also increase.…”
mentioning
confidence: 99%